Overview in the Field of Physical Education and Sports: Leg Power, Agility, Flexibility, and Speed to the T-Kick Ability of Martial Arts Athletes - Suyudi, Imam; Nawir, Nukhrawi; Saleh, M. Sahib; Hudain, Muh. Adnan; Hasyim, Ria Hasyiriani (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This research analyzes the contribution of leg power, agility, flexibility, and speed to the T-kick ability of PPLP Dispora South Sulawesi martial arts athletes. We use quantitative methods with a correlational analysis approach. The results showed that agility made the largest contribution to T-kick ability with 83.3%, followed by leg power at 68.8%. Speed contributed 40.5%, while flexibility contributed the lowest at 24.7%. The combined analysis of the four variables (leg power, agility, flexibility, and speed) on T-kicking ability shows a very significant contribution, namely 96.0%. In conclusion, agility and leg power have a dominant role in improving an athlete's T-kick ability. Even though flexibility has the lowest contribution, the combination of these four factors is very decisive in developing T-kick ability. These findings can be a valuable reference for coaches when designing effective training programs to improve the performance of South Sulawesi Dispora PPLP martial arts athletes.